Evaluating the potential of adaptive comfort approach using historic data to reduce energy consumption in buildings in southern Spain - Bienvenido-Huertas, David (2020)
The application of adaptive comfort models is among the determinant factors to reduce greenhouse gas emissions in the building sector. This research studies the region of Andalusia (south of Spain). A cluster analysis is applied to 786 Andalusian municipalities, and 4 groups are established according to the potential of adaptive strategies. A town is chosen from each group, and an hourly specific study is conducted for the last 20 years, as well as a daily study of the old time series by using an artificial neural network based on the existing climate data. The possibility of application of the EN 16798-1:2019 standard during the days of the year is analysed, as well as the possibilities of using natural ventilation and the possibility of using adaptive setpoint temperatures in comparison with both 3 fixed heating temperatures and 3 fixed cooling temperatures by considering the energy saving. The results to apply the standard ranged 69.0 and 100% of the days of each year. The possibilities of natural ventilation considered were greater than 10% of the hours of the year in all the assumptions. The energy saving of cooling degrees reveals a greater potential in the area studied than that of heating degrees; this tendency is supported by the study of old temporary series which are part of the climate variation predicted throughout the 21st century.